Temperature-Responsive Gelation of Type I Collagen Solutions Involving Fibril Formation and Genipin Crosslinking as a Potential Injectable Hydrogel - Yunoki, Shunji; Ohyabu, Yoshimi; Hatayama, Hirosuke (International Journal of Biomaterials, 2013)
We investigated the temperature-responsive gelation of collagen/genipin solutions using pepsin-solubilized collagen (PSC) and acid-solubilized collagen (ASC) as substrates. Gelation occurred in the PSC/genipin solutions at genipin concentrations 0–2 mM under moderate change in temperature from 25 to 37°C. The PSC/genipin solutions exhibited fluidity at room temperature for at least 30 min, whereas the ASC/genipin solutions rapidly reached gel points. In specific cases PSC would be preferred over ASC as an injectable gel system. The temperature-responsive gelation of PSC/genipin solutions was due to temperature responses to genipin crosslinking and collagen fibril formation. The elastic modulus of the 0.5% PSC/genipin gel system could be adjusted in a range of 2.5 to 50 kPa by the PSC and genipin concentrations, suggesting that a PSC/genipin solution is a potential injectable gel system for drug and cell carriers, with mechanical properties matching those of living tissues.